(untitled) (Vietnam Journal of Community Medicine, 2025)
Digital transformation in healthcare is accelerating the implementation of Electronic Medical Records (EMRs) in medical facilities. This study aims to evaluate the effectiveness of EMRs in healthcare management, identify existing challenges, and propose suitable solutions. A mixed-methods approach was used, including a survey of 125 healthcare staff and in-depth interviews with 10 managers and IT personnel at public hospitals in Ho Chi Minh City, conducted from March to April 2025. The results show that EMRs bring several benefits such as improved information retrieval, support for statistical reporting and management, and reduction of professional errors. However, implementation still faces barriers including inconsistent IT infrastructure, insufficiently trained personnel, and limited system integration and data sharing. Moreover, disparities among hospital levels lead to differences in adoption and utilization. The study recommends a comprehensive EMR implementation strategy, including synchronized investment in infrastructure, human resources, and software, along with data standardization and supportive policies. This is a critical step towards building a smart, efficient, and patient-centered healthcare system.